Sifat Rekomendasi Pengembalian Kerugian Negara Dalam Laporan Hasil Pemeriksaan Badan Pemeriksa Keuangan - Caniago, Candra Feri; Khairani, Khairani; Yuslim, Yuslim (Faculty of Law, Andalas University, 2023)
Recommendations are suggestions from the examiner based on the results of the examination contained in the Audit Report (LHP) of the Supreme Audit Agency (BPK). Law No. 15/2004 mandates that recommendations must be followed up by responsible officials or parties. On several occasions, BPK has stated that its audit results are final and binding. A common recommendation in BPK's LHP is to return state losses to the state or regional treasury by stating the amount of money to be returned. Meanwhile, in other provisions, namely PP No. 38 of 2016 and BPK Regulation No. 3 of 2007, it is stated that the BPK audit results are one of the sources of information on the occurrence of losses, which will then be processed for imposition and compensation claims. In its provisions, all decisions arising from the process may differ from the state losses stated in the BPK's LHP. The purpose of this article is to examine the nature of the recommendations for the recovery of state losses in the BPK's LHP. This research is normative legal research with the approach of principles, cases, laws, and regulations. The results show that the BPK's recommendation is final and binding since the LHP is issued and submitted to the representative institution, so it must be followed up by providing answers and explanations to the BPK. Meanwhile, the state loss stated in the LHP BPK is not final. This is related to the authority of BPK, where the recommendation to recover state losses in the LHP BPK is not in the context of exercising the authority to calculate state losses, as well as assessing and/or determining the amount of state losses.